De Legibus et Consuetudinibus Angliae : Libri Quinque in Varios Tractatus Distincti. Henry de Bracton, Edited by Travers Twiss. - Bracton, Henry de, -1268 (Cambridge library collection. Rolls., 1878)
The thirteenth-century Latin legal treatise best known as Bracton is now thought to be the work of several hands, and Henry de Bracton (d.1268) to have been only the last of these. Work began on it in the 1230s and largely ceased in the early 1250s, but the treatise - an ambitious survey of English law - was never finished. Between 1878 and 1883, the scholar and jurist Sir Travers Twiss (1809-97) edited and published this work in six volumes for the Rolls Series. His text was mainly based on the first printed edition of 1569. Although he provided the first English translation of Bracton, Twiss's work has been criticised and since superseded. Volume 1 contains Book 1 and most of Book 2. These include the general introduction, the law of persons and most of the law of things.